The Influence of Price Perception and Trust on Purchasing Intention of Women’s Care at E-commerce - Haryudi Anas; Pratiwi Nilasari; Rini Wijayaningsih; Andrian (PT FORMOSA CENDEKIA GLOBAL, 2023)
English This study aims to determine how much influence the perception of price and trust have on the intention to buy cosmetics at Shopee. This research is quantitative, using the T-test and F-test with a significance level of 5%. The sampling technique uses the Slovin formula to select 169 respondents. According to the results of testing the hypothesis in this study using the T-test, the price perception variable on buying interest has a T-count value of 5.104 greater than the T-table value of 1.974, so it can be said that the price perception variable has a significant influence on buying interest. The T-test variable of trust in buying interest has a t-count value of 14.116, which is greater than the T-table of 1.974, so it can be said that the trust variable has a significant influence on buying interest. Meanwhile, the results of the F-test showed that there was a positive influence of perceived price and trust on purchase intention, with an F-value of 218.139 and an F-table of 3.05. It can be concluded that perceived price and trust simultaneously had an effect on purchase intention.